260 Gene transfer with rAAVrh74.MHCK7.SGCB increased β-sarcoglycan expression in LGMD type 2E patients. Issue 6 (27th May 2022) - Richardson, James; Rodino-Klapac, Louise; Pozsgai, Eric; Lewis, Sarah; Griffin, Danielle; Lehman, Kelly; Church, Kathleen; Miller, Natalie; Iammarino, Megan; Lowes, Linda; Mendell, Jerry
Abstract : These are initial findings of ongoing, phase 1 multiple ascending-dose gene transfer trial of ≤9 LGMD2E patients who received rAAVrh74.MHCK7.SGCB (NCT03652259 ). Participants: patients 4–15y, confirmed β-sarcoglycan (SGCB) mutation (both alleles), negative for rAAVrh74 antibodies, >40%n on 100-meter timed test. Patients received single IV infusion of 5x1013 vg/kg rAAVrh74.MHCK7.SGCB. Prednisone 1 mg/kg/day was initiated 1d before gene delivery, tapering after 30d. Primary endpoints: ≥20% SGCB-positive fibers (Day-60 muscle biopsy) and safety (Day 270). Secondary endpoints: CK decrease and functional endpoints (Day 270). First 3 patients enrolled (age 13[n=2]; age 4[n=1]): robust SGCB expression observed by immunohistochemistry (IHC), with a mean of 51% SGCB positive fibers (range 42–63%) expressing a mean 47% intensity (range 38–57%). Co-localization of β-sarcoglycan observed (IHC). Western blot showed a mean 36.1% SGCB expression vs normal (range 34–39%). Mean CK levels reduced by 82%, suggesting slowed muscle destruction. Two patients had elevated liver enzymes (1 serious) and 1 had elevated bilirubin following oral steroid taper, which returned to baseline. Two patients had transient mild nausea, corresponding with increased steroid dosing. No other clinically significant lab findings. Gene transfer in LGMD2E patients following rAAVrh74.MHCK7.SGCB infusion was positive for defined endpoints, demon- strating potential benefits of a rationally designed delivery system. jrichardson@sarepta.com